2022
DOI: 10.3389/fsurg.2022.841275
|View full text |Cite
|
Sign up to set email alerts
|

The Best Evidence for the Prevention and Management of Lower Extremity Deep Venous Thrombosis After Gynecological Malignant Tumor Surgery: A Systematic Review and Network Meta-Analysis

Abstract: Background:To search and obtain the relevant evidence of prevention and management of lower extremity deep venous thrombosis (DVT) after gynecological malignant tumor operation and to summarize the relevant evidence.MethodsWe searched the JBI evidence summary, up to date, the national comprehensive cancer network of the United States, the guide library of the National Institute of clinical medicine of the United Kingdom, PubMed, the Chinese biomedical literature database, CNKI, Wanfang, and other relevant evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Laparoscopic surgery is a commonly employed minimally invasive technique within gynecology. Nonetheless, the incidence of LEDVT remains high due to the utilization of pneumoperitoneum and the patient’s position during surgery ( Hu et al, 2022 ; Wu & Cheng, 2020 ). A previous study displayed the incidence of LEDVT subsequent to gynecologic laparoscopic surgery to be 7.6–11.55% ( Tian & Li, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic surgery is a commonly employed minimally invasive technique within gynecology. Nonetheless, the incidence of LEDVT remains high due to the utilization of pneumoperitoneum and the patient’s position during surgery ( Hu et al, 2022 ; Wu & Cheng, 2020 ). A previous study displayed the incidence of LEDVT subsequent to gynecologic laparoscopic surgery to be 7.6–11.55% ( Tian & Li, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have reported that their model has considerable predictive value for LEDVT ( Hu et al, 2022 ; Tian & Li, 2021 ; Wu & Cheng, 2020 ). However, they did not take into account the relevant preoperative biochemical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, leads to venous dilation, endothelial impairment, and the accumulation of coagulation factors that trigger the activation of the coagulation system, ultimately facilitating the development of thrombus. Consequently, numerous scholarly works have emphasized the significance of health education pertaining to mechanical prophylaxis, including healthcare practitioners advising patients to engage in upper limb relaxation and clenching at the site of peripheral central venous catheter insertion as a preventive measure against the formation of PICC-RVTE (20,21). Furthermore, our study specifically examined the association between a history of thrombosis within the previous 12 months and the formation of PICC-RVTE.…”
mentioning
confidence: 99%